1999
DOI: 10.1149/1.1392446
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Coordination in Gel Electrolytes Quantitative Analysis

Abstract: Gel electrolytes, created for use in modern lithium-ion batteries, 1 are complex materials with respect to their composition and to their behavior. The gels consist of a polymer mixed with a lithium salt and a plasticizer. The plasticizer, being an organic solvent able to dissolve the salt, maintains a liquid-like state within the material. At the same time, the polymer gives the gel a mechanical strength approaching that of a solid. Thus, the resulting gel electrolyte can successfully separate the electrodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
(17 reference statements)
1
14
0
Order By: Relevance
“…The affinity between lithium salts and PVdF is known to be very bad, as shown by infrared and Raman spectroscopic studies37, 38 and by NMR studies 39. Some 19 F NMR measurements, performed on our samples, have confirmed the bad affinity between LiPF 6 and PVdF.…”
Section: Resultssupporting
confidence: 61%
“…The affinity between lithium salts and PVdF is known to be very bad, as shown by infrared and Raman spectroscopic studies37, 38 and by NMR studies 39. Some 19 F NMR measurements, performed on our samples, have confirmed the bad affinity between LiPF 6 and PVdF.…”
Section: Resultssupporting
confidence: 61%
“…It has been shown that PVDF and PVDF-HFP, in contrast to polymers based on ethylene oxide, do not take an active part in the conductive mechanism of lithium ions. 25 The aim of the present study was to improve the mechanical properties of solid electrolytes based on a polymethacrylate carrying short PEG side chains by blending them with PVDF-HFP. Crosslinked networks of the polymethacrylate was prepared from a mixture of mono-and difunctional PEG methacrylate macromonomers having PEG chains with a molecular weight of 400 g mol 21 .…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that additions of too large amounts of PVDF‐HFP are detrimental for the conductivity of the blends. PVDF‐HFP does not take an active part in the conduction mechanism of lithium ions and can thus be considered as an inert material in the blend membranes 26…”
Section: Resultsmentioning
confidence: 99%